2019
DOI: 10.1002/14651858.cd007798.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Clinically-indicated replacement versus routine replacement of peripheral venous catheters

Abstract: Background US Centers for Disease Control guidelines recommend replacement of peripheral intravenous catheters (PIVC) no more frequently than every 72 to 96 hours. Routine replacement is thought to reduce the risk of phlebitis and bloodstream infection. Catheter insertion is an unpleasant experience for patients and replacement may be unnecessary if the catheter remains functional and there are no signs of inflammation or infection. Costs associated with routine replacement may be considerable. This is the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
119
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 50 publications
3
119
0
17
Order By: Relevance
“…Also, the poor dressing status may cause the colonization of microorganisms, such as S. aureus, which can lead to severe complications and death [33]. In our study, we observed that approximately 45% of PIVC insertion sites were not visible, a disappointing scenario considering the impact that inspection of the PIVC insertion site per shift would have to prevent and mitigate adverse events [31]. Removal of the PIVC should occur if phlebitis, inflammation or obstruction are present, or intravenous therapy has completed in the previous 24 hours, or the PIVC is no longer needed [4,23,34].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Also, the poor dressing status may cause the colonization of microorganisms, such as S. aureus, which can lead to severe complications and death [33]. In our study, we observed that approximately 45% of PIVC insertion sites were not visible, a disappointing scenario considering the impact that inspection of the PIVC insertion site per shift would have to prevent and mitigate adverse events [31]. Removal of the PIVC should occur if phlebitis, inflammation or obstruction are present, or intravenous therapy has completed in the previous 24 hours, or the PIVC is no longer needed [4,23,34].…”
Section: Discussionmentioning
confidence: 75%
“…The findings related to dressing status, visual inspection, and unnecessary PIVCs were moderate. International evidence recommends that PIVC dressings should be intact, clean, and dry, plus adequately secured and visible during the inspection of insertion site for prevention of PIVC failure [29][30][31]. The 34% of transparent dressings were not in optimal conditions, a rate comparable to the 21-34% of dressings compromised (moist, soiled, inadequately secured, or lifting of the skin) reported previously [1,32].…”
Section: Discussionmentioning
confidence: 99%
“…11,21,22,23 There is agreement among the research that utilizing an objective SPC assessment tool, rather than clinical judgment, aids in the appropriate timing of SPC removal that is supported by this study. 15,17 The inability to obtain and maintain vascular access has significant negative consequences, including delay in treatment, complications leading to prolonged LOS, and costly subsequent medical intervention; whereas maintenance of vascular access can lead to increased nurse time to focus on more acute issues and, most important, improving the patient outcome and experience. 22 Recent studies have evaluated the current placement and maintenance guidelines with regard to prolonging dwell time of an SPC, removing them only when clinically necessary.…”
Section: Discussionmentioning
confidence: 99%
“…13 Additionally, multiple research studies have found fewer or equal occurrences of phlebitis, infiltration, and extravasation in the SPCs replaced when clinically indicated than with those removed routinely in more than 4000 patients. 3,5,14,15 These findings are associated with savings in time, supplies, and health care dollars, as well as increased satisfaction by patients and clinicians.…”
mentioning
confidence: 99%
“…Despite this, recent studies have shown that a longer catheter dwell time increases the risk of catheter-related infections (Mermel, 2017). Additionally, a systematic review published in 2019 reported that the risk of local infection was unclear when PVCs were changed based on clinical indications (Webster, Osborne, Rickard, & Marsh, 2019). Therefore, patients who remain on PVC for longer than the routine indwelling time might be more susceptible to infection.…”
Section: Introductionmentioning
confidence: 99%